Prospective and Challenges: Tourism Development at Meghauli - Subedi, Bishwa Raj (Journal of Advanced Academic Research, 2017)
Background: Meghauli is known as one of the richest villages in Nepal in terms of floura and fauna. It is the heart of beauty that is totally unexpected in a country known mainly for a majestic and powerful location teeming with wild life. It hosts one of Asia’s finest national parks, renowned for its dense concentration of wild life. Tourists can be attracted from all over the world to view the floura and fauna along with other attractions. Objectives: The objective to study the prospective and the challenges of tourism development in Meghauli. Methodology: Descriptive and analytical research designs have been followed. Required information for the study has been obtained both from secondary and primary sources. Result: Some of the prime tourism attractions of Meghauli are the rare flora and fauna, natural beauty, villages, community forest, cultural diversity, religious places, rivers, lakes, world heritage CNP, eco-park, picnic park and the sunset view point. Due to these various tourism attractions, Meghauli has potential for the establishment of magnificent resorts and future development of tourism. Conclusion: Meghauli is situated by the side banks of CNP and two big rivers: Rapti and Narayani. The community forest and CNP are home to many types of wildlife. Almost 500 species of birds and wide variety of vegetations can be found in Meghauli. The dense forests, grasslands, rivers and many lakes embrace a balanced park ecology providing an environment suitable for animals, birds, insects and other forms of life. But it is not managed naturally and properly.